The Impact of Product Innovation and Branding on Sales of Woven Fabrics - Sri Erfanni; Chairul Adhim; Syafrudin Syafrudin (Yayasan Pendidikan Bukhari Dwi Muslim, 2026)
Purpose: This study aims to determine the effect of product innovation and branding on sales of Muna Pa'a woven fabric in Ranggo Village, Pajo Subdistrict. Research Method: This study employed a quantitative, explanatory design. The population consisted of 100 people, all of whom were included in the sample using saturation sampling. Data were collected using a five-point Likert-scale questionnaire and analyzed using multiple linear regression in IBM SPSS. Results and Discussion: The results indicate that, individually, both product innovation and branding have a positive and significant effect on sales of Muna Pa'a woven fabric. Collectively, these two variables also have a positive and significant combined effect on driving sales figures. Implications: These findings suggest that artisans and local governments should integrate pattern/design innovation with a strong brand identity strategy to expand the market sustainably. Originality: This study provides new contextual evidence that bridges the inconsistencies in previous literature, particularly regarding the dynamics of commercializing traditional textile crafts in rural areas.